2008
DOI: 10.1016/j.juro.2008.01.150
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Study of Lower Urinary Tract Symptoms and Erectile Dysfunction

Abstract: Purpose-Several studies have reported that men with lower urinary tract symptoms (LUTS) are more likely to experience erectile dysfunction (ED). All but one of these studies was crosssectional, limiting inferences about whether LUTS precipitate ED.Materials and Methods-The association between LUTS and incident ED was examined prospectively in the Health Professionals Follow-up Study. LUTS were assessed biennially by the American Urological Association Symptom Index, which captures symptoms of frequency, urgenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 20 publications
2
16
1
Order By: Relevance
“…The IIEF-5 and IPSS scores were correlated (p<0.001) to each other. This was similar to the findings of the study done by Mondul et al,20 who claimed that lower urinary tract symptoms referred to by the IPSS is a relevant factor in ED.…”
Section: Discussionsupporting
confidence: 92%
“…The IIEF-5 and IPSS scores were correlated (p<0.001) to each other. This was similar to the findings of the study done by Mondul et al,20 who claimed that lower urinary tract symptoms referred to by the IPSS is a relevant factor in ED.…”
Section: Discussionsupporting
confidence: 92%
“…The risk of ED increased with rising LUTS severity with stronger correlation in younger than in older men. 8 This correlation was proved worldwide as evidenced by the results of the Asian Survey of Aging Males study. This survey was carried out in Asian men aged 50-80 years from five Asian countries.…”
Section: Luts and Ed: Clinical And Epidemiological Correlationsmentioning
confidence: 89%
“…Male LUTS and sexual dysfunction are conditions encountered on a daily basis in urology practice. A great deal of epidemiologic and clinical research has shown that LUTS and sexual dysfunction are strongly linked (Grade B) [77–86]. Multidisciplinary human study is warranted on the basis of the possible common pathogenesis for LUTS and sexual dysfunction (Grade C) [87].…”
Section: Sexual Dysfunction Associated With Lower Urinary Tract Symptmentioning
confidence: 99%